Context-specificity to reduce bias in self-assessments: Comparing teachers' scenario-based self-assessment and objective assessment of technological knowledge - Kastorff, Tamara; Sailer, Michael; Vejvoda, Johanna; Schultz-Pernice, Florian; Hartmann, Valentin; Hertl, Anna; Berger, Sonja; Stegmann, Karsten (Journal of Research on Technology in Education, 2022)
Previous research has focused on self-assessments rather than objective assessments for assessing teachers' technological knowledge (TK). Notwithstanding, empirical studies have failed to show stable relationships between self-assessments and objective assessments. In this study, we investigate the extent to which scenario-based self-assessments of (student) teachers' (N=75) TK can serve as anchors by helping them to identify the relevant skills that are required in concrete and authentic situations and might be therefore effective to bring the results of objective and subjective measures closer together using a path analytical model. Overall, the results suggest that scenario-based self-assessment is promising for the approximation of the results of objective assessment measures, especially for operational technical skills.
CRIS-Team WoS Importer:2022-05-13